The Heart as a Site of Metastasis of Benign Metastasizing Leiomyoma: Case Report and Review of the Literature - Mariam Meddeb; Robert D. Chow; Randolph Whipps; Reyaz Haque (Case Reports in Cardiology)
Uterine leiomyomas are the most common gynecological tumors in premenopausal women. While the lung is the most common extrauterine organ afflicted, benign metastasizing leiomyomas (BML) of the heart are rarities. We report an incidental finding of a cardiac mass in a 36-year-old woman who presented to the Emergency Department after a motor vehicle accident. CT scan of the chest revealed 2 well-circumscribed pulmonary nodules and a filling defect in the right ventricle. Echocardiogram showed a 4 cm mass attached to the right ventricular (RV) septum. The cardiac tumor was resected and showed benign histologic features. Immunohistochemical staining was positive for smooth muscle α-actin and desmin, as well as estrogen and progesterone receptors, consistent with the diagnosis of uterine leiomyoma.